Webinar-Based Health Education on Ergonomic Posture as a Promotive and Preventive Strategy for Musculoskeletal Disorders (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Musculoskeletal disorders are among the most common health problems resulting from non-ergonomic body posture habits during daily activities, particularly among individuals of productive age. Health education plays an important promotive and preventive role in efforts to prevent musculoskeletal disorders. This community service activity aimed to provide education on ergonomic body posture as a promotive and preventive strategy against musculoskeletal disorders through a webinar. The activity was conducted in the form of a webinar featuring dr. Maulana Hasymi Hutabarat, Sp.OT, as the keynote speaker. The material was delivered through an educational presentation followed by an interactive discussion session on the application of ergonomic body posture in daily activities. Participants included students of Sultan Ageng Tirtayasa University (UNTIRTA) as well as members of the general public from various institutional backgrounds. The implementation of the activity demonstrated active participant engagement, particularly during the discussion and question-and-answer sessions. This community service activity is expected to enhance participants’ understanding and awareness of the importance of applying ergonomic body posture and to contribute to promotive and preventive efforts against musculoskeletal disorders.